1990
DOI: 10.1016/0035-9203(90)90073-n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of untreated bed nets on the transmission of Plasmodium falciparum, P. vivax and Wuchereria bancrofti in Papua New Guinea

Abstract: The impact of untreated bed nets on the transmission of human malaria and filariasis in a village in a hyperendemic area of Papua New Guinea was studied. In anopheline mosquitoes, the Plasmodium falciparum sporozoite antigen positivity rate, filarial infection rates and human blood indices dropped significantly after bed nets were introduced. This reduction in human-vector contact did not affect mosquito density as no significant difference in either landing rates or indoor resting catches was found. The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Our results are consistent with evidence that untreated bednets provide less protection than treated ones (Burkot et al, 1990). Our models predict that A. gambiae do not enter houses in lower numbers in ITN-provided rooms compared with houses with untreated nets (Mathenge et al, 2001), but the proportion of unfed and exiting mosquitoes will be significantly greater in treated houses than untreated ones.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with evidence that untreated bednets provide less protection than treated ones (Burkot et al, 1990). Our models predict that A. gambiae do not enter houses in lower numbers in ITN-provided rooms compared with houses with untreated nets (Mathenge et al, 2001), but the proportion of unfed and exiting mosquitoes will be significantly greater in treated houses than untreated ones.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective analysis study in southern Tanzania showed use of an untreated bed net reduced malaria transmission 4.2-fold while adding a longer-lasting insecticide treated bed net was associated with an additional 4.6-fold reduction in malaria transmission (161). In Papua New Guinea, Burkot et al (1990) implemented untreated bed nets and reported a significant reduction in man-vector contact (by looking at the percentage of mosquitoes that fed on humans) as well as sporozoite antigen rates for Plasmodiumfalciparum, but this reduction was not enough to significantly affect parasite rates in the human population or in mosquito density (20). This same study found no significant difference in mosquito density from outdoor or indoor landing after bed net usage (20).…”
Section: Before and After Bed Net Applicationmentioning
confidence: 99%
“…49 ing. The use of bed nets deserves particular attention; this protection measure is very effective when bed nets are treated with insecticides, [35][36][37][38]50 even when some holes normally develop as a result of wear-and-tear. The results of the present study indicate that although untreated nets provide protection, when holes appear this protective effect reverts and the risk of malaria infection increases.…”
Section: No3 Mayo-junio De 2007mentioning
confidence: 99%
“…34 The efficacy of insecticide-impregnated bed nets in conferring high protection against child mortality has been proven in P. falciparum malaria areas. [35][36][37][38] As impregnated bed nets have little effect on morbidity, they have not been recommended for the control of P. vivax malaria. Nevertheless, untreated bed nets have been proven to protect against P. vivax infection in the Lacandon Forest 9 and other endemic areas, 39 and in the present study people that do not use or irregularly use untreated bed nets had a higher risk for P. vivax malaria.…”
Section: No3 Mayo-junio De 2007mentioning
confidence: 99%